THE ROLE OF POLITICAL TECHNOLOGIES IN PUBLIC ADMINISTRATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores the transformative impact of political technologies on public administration, emphasizing their role in enhancing governance, citizen engagement, and policy formulation. With the rise of digital tools and platforms, public institutions can leverage data analytics and social media to improve communication and transparency. The integration of e-government initiatives facilitates efficient service delivery and fosters greater accountability in decision-making processes. By examining case studies and current trends, this article highlights the potential of political technologies to reshape public administration, promoting innovation and responsiveness in a rapidly evolving political landscape.